Answer:
should be A
Step-by-step explanation:
Translated left by 7
Answer:
−7(2x−11)
use distributive property
-7(2x)-7(-11)
-14x+77
Answer:
(x+6)(x−6)=0
x=-6 or x=6
Step-by-step explanation:
X^2 - 36 = 0
Solve by Square Root
add 36 both sides
x^2−36+36=0+36
x^2=36
square root
x=±√36
x=6 or x=−6
You can do that or for 2nd option
Solve by factoring
x^2-36=0
(x+6)(x−6)=0
Set factors equal to 0
x+6=0 or x−6=0
x=-6 or x=6
PLEASE NOTE: 36 is the square of 6
and
x2 is the square of x1
The length of a'b' is the same as ab because it is the same image so it is 3 units
Answer:
<em>f = g/ g+1</em>
Step-by-step explanation:
Remove Parenthesis.
<em>fg - 1 x 5 = g - 1 x f - 1 x 5</em>
Cancel <em>-1 x 5</em> on both sides.
<em>fg = g - 1 x f</em>
Simplify <em>1 x f</em> to f.
<em>fg = g - f</em>
Add <em>f </em>to both sides.
<em>fg + f = g</em>
Factor out the common term <em>f.</em>
<em>f (g + 1) = g</em>
Divide both sides by <em>g + 1</em>
<em>f = g/ g + 1</em>